Bi25FeO40 piezoelectric catalyst as well as preparation method and application thereof
By dissolving bismuth and iron sources in ethylene glycol and carrying out hydrothermal reactions, Bi25FeO40 containing variable ions and oxygen vacancies is formed, which solves the problem of insufficient degradation performance of the catalyst in dark conditions, and significantly improves its in dark conditions. Piezoelectric properties and pollutant degradation capacity.
Patent Information
- Application Number
- CN202411335049.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The existing Bi25FeO40 catalyst has weak performance in degrading pollutants in dark conditions, mainly due to its insufficient polarization electric field strength and lack of variable valence ions and oxygen vacancies defects, resulting in low storage charge concentration and low piezoelectric charge.
By dissolving bismuth and iron sources in ethylene glycol, adjusting the pH value and carrying out hydrothermal reactions, an uneven coordination system is formed, and Bi25FeO40 containing Bi3+/Bi5+, Fe2+/Fe3+ variable ions and oxygen vacancy is enhanced. Piezoelectric characteristics.
The release of stored electrons and holes under mechanical stress under dark conditions is achieved, which significantly improves the degradation ability and cyclic stability of organic pollutants.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of piezoelectric catalytic material preparation, and is specifically a Bi 25 FeO 40 Piezoelectric catalyst and its preparation method and application. Background Art
[0002] Photocatalysts can use the photogenerated charges generated by solar energy to form active free radicals to initiate catalytic reactions, which can control environmental pollution. However, photocatalytic reactions can only be carried out in areas with sufficient sunlight during the day, not in the dark. Piezoelectric catalysts with energy storage characteristics, strong polarization electric field strength, and defects such as variable valence ions and oxygen vacancies can use mechanical force to release stored electrons and holes and generate piezoelectric charges under dark conditions, and are expected to achieve efficient dark catalytic reactions.
[0003] Bi 25 FeO 40 As a common bismuth ferrite-based catalyst, the special spin characteristics of Fe atoms in its structure lead to its weak piezoelectric effect. However, the weak polarization electric field strength makes its own stored charge concentration low and the generated piezoelectric charge small, thus showing weak dark catalytic performance. Chinese patent CN111185184B discloses that bismuth source and iron source are dissolved in ethylene glycol, and then titrated with KOH to prepare Bi with visible light degradation performance of water pollutants such as methylene blue by hydrothermal method. 25 FeO 40 Due to the uniform complexation of ethylene glycol, it has no ability to degrade methylene blue water pollutants under dark conditions. The literature (Chemical Engineering Journal 429 (2022) 132130) discloses that 4 μm cubic Bi was prepared by hydrothermal method using nitric acid as solvent and KOH as mineralizer. 25 FeO 40 , tetracycline is degraded under visible light, but nitric acid prevents the hydrolysis of nitrates and cannot form variable valence ions, resulting in its lack of degradation ability under dark conditions. Chinese patent CN 110975874BA discloses that a bismuth source and an iron source are dissolved in water, then added dropwise to ethanol containing a surfactant, and KOH solution is added dropwise to obtain a Fe-containing 3+ / Fe 2+ A rod-shaped Bi2O3 assembled from nanoparticles of variable valence ions 25 FeO 40, has the performance of visible light-Fenton degradation of tetracycline, but the degradation performance is weak under dark conditions. Chinese patents CN102101700B and CN102091632A reported that ethylene glycol was used as solvent, and the mother salt solution was obtained after the iron source and bismuth source were dissolved. The precursor was obtained by ammonia titration, washing and aging. The microwave hydrothermal method was used to prepare a porous cubic structure of Bi with a size of about 10 μm. 25 FeO 40 -BiFeO 3 Powder and Bi flake structure of about 10 nm 25 FeO 40 The powder has no defects such as variable valence ions or oxygen vacancies due to the uniform complexation of ethylene glycol, which makes it unable to degrade pollutants under dark conditions. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a Bi 25 FeO 40 Piezoelectric catalyst and its preparation method and application, Bi obtained by the preparation method 25 FeO 40 Piezoelectric catalysts have enhanced piezoelectric polarization properties and have a strong ability to degrade pollutants under dark conditions.
[0005] The present invention is achieved through the following technical solutions: A kind of Bi 25 FeO 40 The method for preparing a piezoelectric catalyst comprises the following steps: Step 1: dissolving a bismuth source and an iron source in ethylene glycol at a molar ratio of 1:1, and then adding water to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusting the pH value of the precursor solution to 9-11, precipitating the precipitate, and washing and drying the precipitate in sequence; Step 3: Mix the precipitate with NaOH solution and perform a hydrothermal reaction. After the reaction is completed, wash and dry in sequence to obtain Bi 25 FeO 40 Piezoelectric catalyst.
[0006] Preferably, in step 1, the iron source is Fe(NO 3 ) 3 6H 2 O or FeCl 3 6H 2 O.
[0007] Preferably, in step 1, the bismuth source is Bi(NO 3 ) 3·5H 2 O or BiCl 3 6H 2 O.
[0008] Preferably, in step 1, the total concentration of the iron source and the bismuth source in ethylene glycol is 0.04-0.4 mol / L.
[0009] Preferably, in step 1, the volume ratio of ethylene glycol to water is 50:(40-90).
[0010] Preferably, in step 3, the concentration of the added NaOH solution is 6-10 mol / L.
[0011] Preferably, in step 3, the hydrothermal reaction temperature is 120-160° C., and the hydrothermal reaction time is 8-20 h.
[0012] The present invention provides Bi obtained by the preparation method 25 FeO 40 Piezoelectric catalyst, the Bi 25 FeO 40 The piezoelectric catalyst has a bismuthite structure, a cubic crystal system, a 123 space group, and a microscopic morphology consisting of square nanosheets and nanoparticles.
[0013] The present invention provides the Bi 25 FeO 40 Application of piezoelectric catalysts in catalytic degradation of organic pollutants.
[0014] Preferably, the catalytic degradation of organic pollutants is carried out under dark conditions.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention dissolves the iron source and the bismuth source in ethylene glycol, adds a certain amount of water, and hydrolyzes part of the ethylene glycol to produce acetaldehyde and ethanol, and forms Bi in the solution. 3+ and Fe 3+ Complex with ethylene glycol and Bi 3+ and Fe 3+ The two systems are complexed with ethanol, and the two complex systems polymerize to form an uneven coordination system, which is hydrothermally crystallized to form Bi 3+ and Fe 3+ Square nanosheet structure and Bi 3+ and Fe 3+ The structure of nanoparticles complexed with ethanol has different crystallization rates due to the uneven coordination system, forming Bi 3+ / Bi 5+ , Fe 2+ / Fe 3+ Bi with variable valence ions and oxygen vacancies25 FeO 40 , making Bi 25 FeO 40 The electrons and holes are stored, and the coexistence of the electrons and holes leads to the formation of a polarization electric field. The present invention utilizes the different crystallization rates caused by the uneven coordination system to make the Bi prepared by the present invention 25 FeO 40 It has strong piezoelectric properties and can release stored electrons and holes under mechanical stress in dark conditions to degrade and mineralize organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 Bi prepared in Examples 1-6 of the present invention 25 FeO 40 XRD pattern of .
[0018] Figure 2 The Bi prepared in Example 3 of the present invention 25 FeO 40 SEM image of .
[0019] Figure 3 The Bi prepared in Example 3 of the present invention 25 FeO 40 TEM image of.
[0020] Figure 4 The Bi prepared in Example 3 of the present invention 25 FeO 40 HRTEM image of.
[0021] Figure 5 Bi prepared in Examples 1-4 of the present invention 25 FeO 40 O 1s high-resolution XPS pattern.
[0022] Figure 6 Bi prepared in Examples 1-4 of the present invention 25 FeO 40 High-resolution XPS pattern of Fe 2p.
[0023] Figure 7 Bi prepared in Examples 1-4 of the present invention 25 FeO40 Bi 4f high-resolution XPS pattern.
[0024] Figure 8 Bi prepared in Examples 1-6 of the present invention 25 FeO 40 Piezoelectric current diagram generated by eddy current shear force.
[0025] Fig. 9 The Bi prepared in Example 1 of the present invention 25 FeO 40 Phase change diagram.
[0026] Fig.10 The Bi prepared in Example 2 of the present invention 25 FeO 40 Phase change diagram.
[0027] Fig.11 The Bi prepared in Example 3 of the present invention 25 FeO 40 Phase change diagram.
[0028] Fig.12 The Bi prepared in Example 4 of the present invention 25 FeO 40 Phase change diagram.
[0029] Fig.13 The Bi prepared in Example 1 of the present invention 25 FeO 40 Amplitude variation diagram.
[0030] Fig.14 The Bi prepared in Example 2 of the present invention 25 FeO 40 Amplitude variation diagram.
[0031] Fig.15 The Bi prepared in Example 3 of the present invention 25 FeO 40 Amplitude variation diagram.
[0032] Fig.16 The Bi prepared in Example 4 of the present invention 25 FeO 40 Amplitude variation diagram.
[0033] Fig.17 The Bi prepared in Example 3 of the present invention 25 FeO 40 Absorbance curve of 20 mg / L methylene blue in dark conditions.
[0034] Fig.18The Bi prepared in Example 3 of the present invention 25 FeO 40 EPR pattern of holes under dark conditions.
[0035] Fig.19 Bi prepared in Examples 1-6 of the present invention 25 FeO 40 Degradation curve of 20 mg / L tetracycline in dark conditions.
[0036] Fig. 20 Bi obtained in Example 3 of the present invention is prepared 25 FeO 40 TOC removal efficiency of 40 mg / L tetracycline under dark conditions.
[0037] Fig.21 The Bi prepared in Example 3 of the present invention 25 FeO 40 Cyclic degradation of 20 mg / L tetracycline under dark conditions.
[0038] Fig. 22 The Bi prepared in Example 3 of the present invention 25 FeO 40 Figure 2. Active species capture under dark conditions.
[0039] Fig.23 Bi obtained in Example 3 of the present invention is prepared 25 FeO 40 LC-MS graph of the reaction solution when 20 mg / L tetracycline was degraded in the dark for 5 minutes.
[0040] Fig.24 Bi obtained in Example 3 of the present invention is prepared 25 FeO 40 LC-MS graph of the reaction solution after degrading 20 mg / L tetracycline for 30 min under dark conditions.
[0041] Fig.25 Bi obtained in Example 3 of the present invention is prepared 25 FeO 40 Degradation absorbance change diagram of a mixed solution of 20 mg / L ciprofloxacin, 10 mg / L rhodamine B, 20 mg / L methylene blue, 10 mg / L methylene orange and 20 mg / L tetracycline under dark conditions. DETAILED DESCRIPTION
[0042] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0043] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0044] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0045] The Bi of the present invention 25 FeO 40 The method for preparing a piezoelectric catalyst comprises the following steps: Step 1: dissolving a bismuth source and an iron source in ethylene glycol at a molar ratio of 1:1, and adding water after they are completely dissolved to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjust the pH value of the precursor solution to 9-11, quickly produce precipitation, and wash and dry the precipitate in sequence; Step 3: Mix the above precipitate with NaOH solution and perform hydrothermal reaction. After the reaction is completed, wash and dry in sequence to prepare Bi 25 FeO 40 Piezoelectric catalyst.
[0046] In the present invention, the iron source is preferably Fe(NO 3 ) 3 6H 2 O or FeCl 3 6H 2 O. The bismuth source is preferably Bi(NO 3 ) 3 ·5H 2 O or BiCl 3 6H 2 O.
[0047] In step 1 of the present invention, the total concentration of the iron source and the bismuth source in ethylene glycol is 0.04-0.4 mol / L. The volume ratio of the added ethylene glycol to water is 50:(40-90).
[0048] In step 3 of the present invention, the concentration of the added NaOH solution is 6-10 mol / L, the hydrothermal reaction temperature is 120-160° C., and the hydrothermal reaction time is 8-20 h.
[0049] The Bi prepared by the present invention 25 FeO 40 It has a soft bismuth ore structure, cubic crystal system, 123 space group, and its microscopic morphology is composed of square nanosheets and nanoparticles. It has piezoelectric properties and can store electrons and holes at the same time. 25 FeO 40 , d 33 The value is 1.25 ~7.43 nm·V -1 , the largest d 33 The value is 7.43 nm / V, and the maximum concentrations of stored electrons and holes are 13.18 μmol·g -1 and 129.15 μmol·g -1 .
[0050] The Bi prepared by the present invention 25 FeO 40 In dark conditions 25 FeO 40 Mechanical strain occurs to release stored electron holes and generate piezoelectric charges, which have a good degradation effect on antibiotics and mixed pollutants and have good cycle stability.
[0051] Preferably, the antibiotic is tetracycline. The mixed pollutant is a mixed pollutant of tetracycline, ciprofloxacin, methylene blue, rhodamine B and methylene orange.
[0052] Example 1 Step 1: Fe(NO 3 ) 3 6H 2 O and Bi(NO 3 ) 3 ·5H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.06 mol / L. After it was completely dissolved, 90 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 10, quickly produces precipitation, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 6 mol / L NaOH solution was added and kept at 160 °C for 20 h. After the reaction was completed, it was washed and dried in sequence to prepare Bi 25 FeO 40 Piezoelectric catalyst.
[0053] Example 2 Step 1: Fe(NO 3 ) 3 6H 2 O and Bi(NO 3 ) 3 ·5H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.08 mol / L. After it was completely dissolved, 90 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 10, quickly produces precipitation, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 6 mol / L NaOH solution was added and kept at 160°C for 20 h. After the reaction was completed, it was washed and dried in sequence to prepare Bi 25 FeO 40 Piezoelectric catalyst.
[0054] Example 3 Step 1: Fe(NO 3 ) 3 6H 2 O and Bi(NO 3 ) 3 ·5H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.1 mol / L. After it was completely dissolved, 90 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 10, quickly produces precipitation, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 6 mol / L NaOH solution was added and kept at 160 °C for 20 h. After the reaction was completed, it was washed and dried in sequence to prepare Bi 25 FeO 40 Piezoelectric catalyst.
[0055] Example 4 Step 1: Add Fe(NO 3 ) 3 6H 2 O and Bi(NO 3 ) 3 ·5H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.2 mol / L. After it was completely dissolved, 90 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 10, quickly produces precipitation, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 6 mol / L NaOH solution was added and kept at 160 °C for 20 h. After the reaction was completed, it was washed and dried in sequence to prepare Bi 25 FeO 40 Piezoelectric catalyst.
[0056] Example 5 Step 1: Fe(NO 3 ) 3 6H 2 O and Bi(NO 3 ) 3 ·5H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.3 mol / L. After it was completely dissolved, 90 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 10, quickly produces precipitation, and washes and dries the precipitate in sequence; Step 3: The precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 6 mol / L NaOH solution was added and kept at 160 °C for 20 h. After the reaction was completed, it was washed and dried in sequence to prepare Bi 25 FeO 40 Piezoelectric catalyst.
[0057] Example 6 Step 1: Fe(NO 3 ) 3 6H 2 O and Bi(NO 3 ) 3 ·5H 2O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.4 mol / L. After it was completely dissolved, 90 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 10, quickly produces precipitation, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 6 mol / L NaOH solution was added and kept at 160 °C for 20 h. After the reaction was completed, it was washed and dried in sequence to prepare Bi 25 FeO 40 Piezoelectric catalyst.
[0058] Example 7 Step 1: Fe(NO 3 ) 3 6H 2 O and Bi(NO 3 ) 3 ·5H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.06 mol / L. After it was completely dissolved, 60 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 9, quickly produces a precipitate, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 6 mol / L NaOH solution was added and kept at 160 °C for 20 h. After the reaction was completed, it was washed and dried in sequence to prepare Bi 25 FeO 40 Piezoelectric catalyst.
[0059] Example 8 Step 1: Add FeCl 3 6H 2 O and Bi(NO 3 ) 3 ·5H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.04 mol / L. After it was completely dissolved, 80 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 10.2, quickly produces a precipitate, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 8 mol / L NaOH solution was added, and the mixture was kept at 120 °C for 8 h. After the reaction was completed, the mixture was washed and dried in sequence to obtain Bi 25 FeO 40 Piezoelectric catalyst.
[0060] Example 9 Step 1: Add FeCl 3 6H 2 O and BiCl 3 6H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.15 mol / L. After it was completely dissolved, 70 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 10.3, quickly generates precipitation, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 8 mol / L NaOH solution was added, and the mixture was kept at 160 °C for 10 h. After the reaction was completed, the mixture was washed and dried in sequence to obtain Bi 25 FeO 40 Piezoelectric catalyst.
[0061] Example 10 Step 1: Add FeCl 3 6H 2 O and BiCl 3 6H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.08 mol / L. After it was completely dissolved, 70 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 9.5, quickly produces a precipitate, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 7 mol / L NaOH solution was added and kept at 150 °C for 12 h. After the reaction was completed, it was washed and dried in sequence to prepare Bi 25 FeO 40 Piezoelectric catalyst.
[0062] Embodiment 11 Step 1: Add FeCl 3 6H 2 O and BiCl3 6H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 at a concentration of 0.07 mol / L, and after it was completely dissolved, 70 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 10.8, quickly generates precipitation, and washes and dries the precipitate in sequence; Step 3: The precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 9 mol / L NaOH solution was added, and the mixture was kept at 130 °C for 9 h. After the reaction was completed, the precipitate was washed and dried in sequence to obtain Bi 25 FeO 40 Piezoelectric catalyst.
[0063] Example 12 Step 1: Add FeCl 3 6H 2 O and Bi(NO 3 ) 3 ·5H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.25 mol / L. After it was completely dissolved, 70 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 9.8, quickly produces a precipitate, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 7 mol / L NaOH solution was added, and the mixture was kept at 130 °C for 8 h. After the reaction was completed, the mixture was washed and dried in sequence to obtain Bi 25 FeO 40 Piezoelectric catalyst.
[0064] Example 13 Step 1: Fe(NO 3 ) 3 6H 2 O and BiCl 3 6H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.09 mol / L. After it was completely dissolved, 50 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 9.5, quickly produces a precipitate, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 8 mol / L NaOH solution was added, and the mixture was kept at 140 °C for 11 h. After the reaction was completed, the mixture was washed and dried in sequence to obtain Bi 25 FeO 40 Piezoelectric catalyst.
[0065] Embodiment 14 Step 1: Fe(NO 3 ) 3 6H 2 O and BiCl 3 6H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.08 mol / L. After it was completely dissolved, 30 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 10.3, quickly generates precipitation, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 7.5 mol / L NaOH solution was added and kept at 145 °C for 15 h. After the reaction was completed, it was washed and dried in sequence to prepare Bi 25 FeO 40 Piezoelectric catalyst.
[0066] Embodiment 15 Step 1: Add FeCl 3 6H 2 O and Bi(NO 3 ) 3 ·5H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.07 mol / L. After it was completely dissolved, 80 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 11, quickly produces a precipitate, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 9 mol / L NaOH solution was added, and the mixture was kept at 120 °C for 8 h. After the reaction was completed, the mixture was washed and dried in sequence to obtain Bi 25 FeO 40 Piezoelectric catalyst.
[0067] Example 16 Step 1: Fe(NO 3 ) 3 6H 2 O and BiCl 3 6H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.08 mol / L. After it was completely dissolved, 50 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 10.3, quickly generates precipitation, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 9 mol / L NaOH solution was added and kept at 150 °C for 20 h. After the reaction was completed, it was washed and dried in sequence to prepare Bi 25 FeO 40 Piezoelectric catalyst.
[0068] Embodiment 17 Step 1: Fe(NO 3 ) 3 6H 2 O and BiCl 3 6H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.09 mol / L. After it was completely dissolved, 60 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 9.6, quickly generates precipitation, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 9 mol / L NaOH solution was added, and the mixture was kept at 120 °C for 8 h. After the reaction was completed, the mixture was washed and dried in sequence to obtain Bi 25 FeO 40 Piezoelectric catalyst.
[0069] Embodiment 18 Step 1: Add FeCl 3 6H 2 O and Bi(NO 3 ) 3 ·5H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.4 mol / L. After it was completely dissolved, 60 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH3 ·H 2 O adjusts the pH value of the precursor solution to 9.5, quickly produces a precipitate, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 7 mol / L NaOH solution was added, and the mixture was kept at 160 °C for 8 h. After the reaction was completed, the mixture was washed and dried in sequence to obtain Bi 25 FeO 40 Piezoelectric catalyst.
[0070] Embodiment 19 Step 1: Fe(NO 3 ) 3 6H 2 O and BiCl 3 6H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.05 mol / L. After complete dissolution, 40 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 9, quickly produces a precipitate, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 6 mol / L NaOH solution was added, and the mixture was kept at 120 °C for 8 h. After the reaction was completed, the precipitate was washed and dried in sequence to obtain Bi 25 FeO 40 Piezoelectric catalyst.
[0071] Embodiment 20 Step 1: Fe(NO 3 ) 3 6H 2 O and Bi(NO 3 ) 3 ·5H 2 O was dissolved in 50 ml of ethylene glycol at a molar ratio of 1:1 and a concentration of 0.08 mol / L. After it was completely dissolved, 70 mL of deionized water was added to form a precursor solution; Step 2: With stirring, pass NH 3 ·H 2 O adjusts the pH value of the precursor solution to 10.5, quickly generates precipitation, and washes and dries the precipitate in sequence; Step 3: The above precipitate was transferred to a polytetrafluoroethylene reactor, and 40 ml of 8 mol / L NaOH solution was added, and the mixture was kept at 160 °C for 15 h. After the reaction was completed, the mixture was washed and dried in sequence to obtain Bi25 FeO 40 Piezoelectric catalyst.
[0072] The above conclusions and mechanisms are explained in detail below.
[0073] Figure 1 Bi prepared in Examples 1, 2, 3, 4, 5 and 6 of the present invention 25 FeO 40 XRD pattern of the piezoelectric catalyst. The strong diffraction peaks at 2θ=24.7°, 27.6°, 30.4° and 32.9° correspond to Bi 25 FeO 40 The (220), (310), (222) and (321) crystal planes of the sample prepared in the present invention indicate that the sample is Bi2O3 with a bismuthite structure. 25 FeO 40 , belongs to the cubic crystal system and 123 space group.
[0074] Figure 2 and Figure 3 are respectively Bi prepared in Example 1 of the present invention 25 FeO 40 From the SEM and TEM images, it can be observed that the microstructure is composed of square nanosheets of about 500 nm and amorphous nanoparticles. Figure 4 Bi prepared in Example 3 of the present invention 25 FeO 40 In the HRTEM image, clear lattice fringes can be observed, and the lattice spacing is 3.22 nm, corresponding to Bi 25 FeO 40 (310) crystal plane.
[0075] Figure 5 Bi prepared in Examples 1, 2, 3 and 4 of the present invention 25 FeO 40 The high-resolution O 1s spectrum of Example 1, Example 2, Example 3 and Example 4 has three peaks at about 5310.1 eV, 531.6 eV and 532.3 eV, which correspond to lattice oxygen, oxygen vacancies and surface adsorbed hydroxyl oxygen, respectively. The peak areas of Bi prepared in Example 1, Example 2, Example 3 and Example 4 are calculated. 25 FeO 40 The oxygen vacancy contents of are 27.24%, 22.8%, 47.59% and 41.52% respectively. The presence of oxygen vacancies improves the charge storage capacity.
[0076] Figure 6 Bi prepared in Examples 1, 2, 3 and 4 of the present invention 25 FeO40 The high-resolution Fe2p spectrum of the Fe2p spectrum shows that the peak at around 710.2 eV corresponds to Fe 2+ The peaks at around 713.2 eV and 724.8 eV correspond to Fe 3+ , calculated by peak area, the Bi prepared in Example 1, Example 2, Example 3 and Example 4 25 FeO 40 Fe 2+ The contents are 21.62%, 66.27%, 14.06% and 44.87% respectively. Figure 7 Bi prepared in Examples 1, 2, 3 and 4 of the present invention 25 FeO 40 The high-resolution Bi 4f peak can be divided into two pairs of double peaks, 158.62 / 163.97 eV and 159.64 / 165 eV are respectively attributed to the +3-valent bismuth ion and the +5-valent bismuth ion. The Bi prepared in Example 1, Example 2, Example 3 and Example 4 is calculated by peak area. 25 FeO 40 Bi 3+ The contents are 73.92%, 61.46%, 67.38% and 56.21% respectively, Bi 5+ The contents are 26.08%, 38.54%, 32.62% and 43.79% respectively. 2+ / Fe 3+ 、Bi 3+ / Bi +5 The existence of variable valence ion defects further increases the Bi 25 FeO 40 The ability to store charge.
[0077] Figure 8 Bi prepared in Examples 1, 2, 3, 4, 5 and 6 of the present invention 25 FeO 40 Under dark conditions, applying eddy current shear force resulted in a current response, while turning off the eddy current shear force resulted in no current response, which proved that the Bi prepared by the present invention could be 25 FeO 40 It exhibits an obvious piezoelectric response under dark conditions, indicating that it has piezoelectric properties.
[0078] Fig. 9 , Fig.10 , Fig.11 and Fig.12 Bi prepared in Examples 1, 2, 3 and 4 of the present invention are 25 FeO 40The phase change diagram shows that after applying a 10 V bias voltage, the phase angle flips by about 180°, proving that the dipole is easily transformed by an external electric field.
[0079] Fig.13 , Fig.14 , Fig.15 and Fig.16 Bi prepared in Examples 1, 2, 3 and 4 of the present invention are 25 FeO 40 The amplitude change diagram shows a typical "butterfly-shaped curve" under the action of the electric field, which produces a strain-electric field hysteresis phenomenon, proving that it has an obvious piezoelectric response. The piezoelectric "butterfly-shaped curve" is used to calculate d 33 The values are 1.25 nm·V -1 、5.88 nm·V -1 、7.43 nm·V -1 and 6.36 nm·V -1 , Example 3 has a stronger piezoelectric effect, which is consistent with the piezoelectric current result.
[0080] Fig.17 Bi prepared in Example 3 of the present invention 25 FeO 40 The absorbance curve of 20 mg / L methylene blue in dark conditions. The electron concentration stored in methylene blue can be calculated by calculating the absorbance curve of methylene blue. The electron concentration released after 30 minutes of dark reaction is 13.18 μmol·g -1 . Fig.18 Bi prepared in Example 3 of the present invention 25 FeO 40 The EPR of holes at different times in dark conditions was calculated by the spin number, and the hole concentration released after 20 min in dark conditions was 129.15 μmol·g -1 This shows that due to Bi 25 FeO 40 The existence of the polarization electric field promotes the separation of electrons and holes and realizes the simultaneous storage of electrons and holes.
[0081] Fig.19 Bi prepared in Examples 1, 2, 3, 4, 5 and 6 of the present invention 25 FeO 40The degradation curve of 20 mg / L tetracycline under dark conditions shows that after 5 min under dark conditions, the degradation rates of Example 1, Example 2, Example 3, Example 4, Example 5 and Example 6 are 37.80%, 46.06%, 52.73%, 49.74%, 46.30% and 26.60%, respectively. This is due to the fact that under the action of mechanical force, the tetracycline stored in Bi 25 FeO 40 Rapid release of electrons and holes. In 5-30 min, due to Bi 25 FeO 40 The piezoelectric effect of the mechanical force will generate piezoelectric charges to participate in the catalytic degradation reaction. After 30 minutes, the Bi prepared in Example 1, Example 2, Example 3, Example 4, Example 5 and Example 6 25 FeO 40 The degradation rates of tetracycline can reach 52.10%, 62.58%, 81.30%, 72.30%, 74.25% and 36.30% respectively. 25 FeO 40 The degradation rates of tetracycline were the highest at 5 min and 30 min, which was due to its excellent charge storage capacity and piezoelectric effect.
[0082] Fig. 20 Bi prepared in Example 3 of the present invention 25 FeO 40 TOC removal rate of 40 mg / L tetracycline under dark conditions. 25 FeO 40 Under dark conditions, the removal rate of 40 mg / L tetracycline can reach 71.04% after 5 min, and 71.78% after 30 min, indicating that Bi 25 FeO 40 It has strong mineralization ability for tetracycline.
[0083] Fig.21 Bi prepared in Example 3 of the present invention 25 FeO 40 The degradation diagram of 20 mg / L tetracycline under dark conditions shows that the degradation rate of the first cycle is 81.3%. Although the stored charge is continuously consumed with the increase of the number of cycles, the degradation rate can still reach 57.65% after five cycles, which shows that the Bi prepared by the present invention is 25 FeO 40 Has good cycle stability.
[0084] Fig. 22 The Bi prepared in Example 3 of the present invention 25 FeO 40Active species capture diagram under dark conditions. tert-Butanol, p-benzoquinone, sodium oxalate and copper sulfate are used as ·OH, ·O 2 - 、h + and e - The capture agent, compared with the degradation rate of 81.3% without the introduction of the capture agent, after adding the capture agent, the Bi prepared in Example 3 25 FeO 40 The degradation rates of ·OH, ·O 2 - 、h + and e - They all play a role in the degradation process.
[0085] Fig.23 and Fig.24 They are respectively Bi obtained in Preparation Example 3 of the present invention 25 FeO 40 LC-MS images of the reaction solution after 5 min and 30 min of degradation of 20 mg / L tetracycline under dark conditions. At 5 min of dark reaction, intermediates with mass-to-charge ratios (m / z) of 64, 102, 110, 139, 163, 195, 326, 383, 427 and 437 were detected in the tetracycline degradation solution; after 30 min, intermediates with m / z of 64, 120, 122, 163, 219 and 306 were detected. The disappearance of molecules with large mass-to-charge ratios indicated that Bi 25 FeO 40 The actual mineralization degradation process of tetracycline.
[0086] Fig.25 Bi prepared in Example 3 of the present invention 25 FeO 40 The degradation absorbance change diagram of the mixed solution of 20 mg / L ciprofloxacin, 10 mg / L rhodamine B, 20 mg / L methylene blue, 10 mg / L methylene orange and 20 mg / L tetracycline under dark conditions. As time goes by, the absorption intensity gradually weakens. After 30 minutes of reaction, the absorption intensity decreases significantly, indicating that the prepared Bi 25 FeO 40 Piezoelectric catalysts are universal for water pollutants and can degrade antibiotics and dyes.
[0087] The Bi prepared by the present invention 25 FeO 40 Piezoelectric catalysts have strong polarization electric fields as well as oxygen vacancies and variable valence ion defects, which improve the ability to store charge and generate piezoelectric charge. Under mechanical force in dark conditions, Bi 25FeO 40 Piezoelectric catalysts have the ability to efficiently mineralize antibiotics and universally degrade a variety of water pollutants.
[0088] The above is only one embodiment of the present invention, not all or the only embodiment. Any equivalent changes made to the technical solution of the present invention by ordinary technicians in this field after reading the specification of the present invention are covered by the claims of the present invention.
Claims
1. A Bi 25 FeO 40 A method for preparing a piezoelectric catalyst, characterized in that: The following steps are involved: Step 1: dissolving a bismuth source and an iron source in ethylene glycol at a molar ratio of 1:1, and then adding water to form a precursor solution; Step 2: Under stirring, adjust the pH value of the precursor solution to 9-11 by adding NH3·H2O to precipitate, and wash and dry the precipitate in turn; Step 3: Mix the precipitate with NaOH solution and perform a hydrothermal reaction. After the reaction is completed, wash and dry in sequence to obtain Bi 25 FeO 40 Piezoelectric catalyst.
2. Bi according to claim 1 25 FeO 40 A method for preparing a piezoelectric catalyst, characterized in that: In step 1, the iron source is Fe(NO3)3·6H2O or FeCl3·6H2O.
3. Bi according to claim 1 25 FeO 40 A method for preparing a piezoelectric catalyst, characterized in that: In step 1, the bismuth source is Bi(NO3)3·5H2O or BiCl3·6H2O.
4. Bi according to claim 1 25 FeO 40 A method for preparing a piezoelectric catalyst, characterized in that: In step 1, the total concentration of the iron source and the bismuth source in ethylene glycol is 0.04-0.4 mol / L.
5. Bi according to claim 1 25 FeO 40 A method for preparing a piezoelectric catalyst, characterized in that: In step 1, the volume ratio of ethylene glycol to water is 50:(40-90).
6. Bi according to claim 1 25 FeO 40 A method for preparing a piezoelectric catalyst, characterized in that: In step 3, the concentration of the added NaOH solution is 6-10 mol / L.
7. Bi according to claim 1 25 FeO 40 A method for preparing a piezoelectric catalyst, characterized in that: In step 3, the hydrothermal reaction temperature is 120-160 °C, and the hydrothermal reaction time is 8-20 h.
8. Bi obtained by the preparation method according to any one of claims 1 to 7 25 FeO 40 A piezoelectric catalyst, characterized in that The Bi 25 FeO 40 The piezoelectric catalyst has a bismuthite structure, a cubic crystal system, a 123 space group, and a microscopic morphology consisting of square nanosheets and nanoparticles.
9. Bi according to claim 8 25 FeO 40 Application of piezoelectric catalysts in catalytic degradation of organic pollutants.
10. The use according to claim 9, characterized in that: The catalytic degradation of organic pollutants is carried out under dark conditions.
Citation Information
Patent Citations
Method for preparing sillenite powder by microwave-hydrothermal method
CN102101700A
Preparation method of one-dimensional nano Bi25FeO40 material capable of generating photocurrent
CN102701287A
Preparation method and catalytic application of magnetic Bi25FeO40 nanomaterial
CN110975874A
Preparation method of bismuth ferrite visible-light-induced photocatalyst and application of photocatalytic performance of bismuth ferrite visible-light-induced photocatalyst
CN111185184A
BFO / BOC compound with piezoelectric catalysis characteristic as well as preparation method and application of BFO / BOC compound
CN114682281A
